(untitled) (Revista Ciência Agronômica, 2020)
The intrinsic characteristics of the vegetative propagule may influence the rooting speed and shoot growth, as well as the final physiological quality of clonal seedlings of Coffea canephora. The aim of this study was to evaluate the growth and physiological quality of ‘Robusta’ coffee seedlings produced from propagules (stem cuttings) with different cutting ages. The study was conducted in a greenhouse, in the district of Ouro Preto do Oeste, in Rondônia, Brazil (10˚45’43” S and 62˚15’10” W). The ages of the cuttings were 30, 60, 90, 120 and 150 days, corresponding to five positions on the secondary orthotropic stem (sprout), from the apex to the base. Dry matter accumulation, and relative and absolute growth rates were evaluated for 188 days after cutting, as well as the vegetative characteristics of the seedlings at 125 days after cutting. It appears that growth can be divided into three phases: 1) Initial: slow growth, lasting approximately 83 days; 2) Intermediate: fast growth, lasting approximately 40 days; and 3) Final: slow growth, starting approximately 125 days after cutting. With physiological quality, although all the cuttings showed similar growth curves, those of 60, 90 and 120 days produced, 125 days after cutting, the best vegetative performance in the seedlings.